2015
DOI: 10.1016/j.jcrs.2014.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of a new toric presbyopia-correcting posterior chamber silicone intraocular lens

Abstract: Dr. Pepose is a consultant to Bausch & Lomb and was medical monitor of this study. Drs. Buckhurst, Whitman, Feinerman, Hovanesian, Davies, Labor, and Carter are consultants to Bausch & Lomb. At the time of the study, Drs. Hayashida, and Khodai were employees of Bausch & Lomb. Drs. Colvard and Mittleman have financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The results of this study are consistent with the favorable safety and efficacy outcomes demonstrated in the FDA registration trial of the lens [ 8 ]. The inclusion and exclusion criteria for this study were chosen to have a study population somewhat similar to the study population in the FDA trial yet still reflect real-world clinical practice.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study are consistent with the favorable safety and efficacy outcomes demonstrated in the FDA registration trial of the lens [ 8 ]. The inclusion and exclusion criteria for this study were chosen to have a study population somewhat similar to the study population in the FDA trial yet still reflect real-world clinical practice.…”
Section: Discussionsupporting
confidence: 86%
“…The aspheric optic of the parent IOL provides excellent image sharpness [ 6 ] and depth of focus [ 7 ]. On the basis of favorable refractive and visual outcomes in a FDA registration trial [ 8 ], in 2013, the Trulign toric IOL became the first premium presbyopia-correcting toric IOL available for use in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PCO has been reduced, but not eliminated, by more extensive removal or repositioning of lens tissue during surgery, advances in the composition and conformation of IOLs, and posterior capsulorhexis. 8,13,[44][45][46][47][48][49] While certain drugs may impede the initial response of cells to surgery, it is uncertain whether they would continue to block development of PCO that may arise months or years later. 13,20,[50][51][52] Cytotoxic drugs and chemicals that nonspecifically kill cells at the time of surgery and extensive removal of lens epithelial cells may cause the IOL to be more mobile, and drugs may diffuse to surrounding ocular tissues and initiate an inflammatory response to necrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in contrast sensitivity is a side effect of diffractive multifocal IOLs compared with monofocal IOLs. 9,19,20 HOAs and MTFs were measured by the i-Trace based on ray tracing and compared between groups in this study to evaluate the potential effect on the visual and ocular optical quality. The level of HOA is difficult to express when aberrometry is performed for multifocal lenses, 21 and ray tracing seems to be the most adequate platform.…”
Section: Discussionmentioning
confidence: 99%